PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING (CTL) PADA PEMAHAMAN PEMBELAJARAN MATEMATIKA SISWA SD KELAS II - Endah Amalia; Deri Fadhli Pratama (IKIP Siliwangi, 2021)
AbstractThis study aims to examine the learning of mathematics understanding in grade II students using the Contextual Teaching Learning (CTL) learning model. The research method used is descriptive qualitative. The subjects in this study were students of class II SDN 050 Cibiru Bandung City with a total of 28 students consisting of 16 male students and 12 female students. The instruments used were teacher and student observation sheets, math questions, and teacher and student questionnaires. The results showed that there was an increase in the quality of learning after using the CTL learning model. This is indicated by the average value of class mathematics understanding of 79.50 which is in the good category, the highest score of students is 100 and the lowest score is 60. Students' learning completeness shows 96.4% of students get scores above the minimum completeness criteria and 3, 6% still scored below the minimum completeness criteria value.Keywords: Contextual Teaching Learning (CTL), Mathematic Understanding, elementary school studentAbstrakPenelitian ini bertujuan untuk menelaah pembelajaran pemahaman matematika pada siswa kelas II dengan model pembelajaran Contextual Teaching Learning (CTL). Metode penelitian yang digunakan adalah deskriptif kualitatif. Subjek dalam penelitian ini adalah siswa kelas II SDN 050 Cibiru Kota Bandung dengan jumlah siswa sebanyak 28 orang yang terdiri dari 16 orang siswa laki-laki dan 12 orang siswa perempuan. Instrumen yang digunakan adalah lembar observasi guru dan siswa, soal matematika, serta angket guru dan siswa. Hasil penelitian menunjukan bahwa terdapat peningkatan kualitas pembelajaran setelah menggunakan model pembelajaran CTL. Hal tersebut ditunjukan dengan nilai rata-rata pemahaman matematika kelas sebesar 79,50 yang tergolong dalam kategori baik, nilai tertinggi siswa sebesar 100 dan nilai terendah sebesar 60. Ketuntasan belajar siswa menunjukan 96,4% siswa mendapatkan nilai diatas kriteria ketuntasan minimum dan 3,6% masih mendapat nilai dibawah nilai kriteria ketuntasan minimum.Kata kunci : Penerapan kontekstual (CTL), pemahaman matematika, siswa sekolah dasar